Urgensi Penyempurnaan Sistem Norma Klasifikasi Kbli Tanpa Pengampu - Jayaputeri, Tiara; Putra, Mohamad Fajri Mekka (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The OSS system was developed by BKPM as a method to make it easier for Business Actors to start a business in Indonesia. In OSS, created a classification called KBLI which is a reference to classify Indonesian economic activities or activities into several business fields which are distinguished based on the type of economic activity that produces products in the form of goods or services. One of the obstacles in determining the classification norm is when the KBLI code desired by prospective investors could not been selected or when the selection of business fields is replied with a notification which basically states that the selected business field is waiting for confirmation of the Norms, Standards, Procedures and Criteria (NSPK) from the relevant Ministry or Institution, meaning that the selected KBLI is included in the KBLI without a supervisor or is included in the 353 KBLI that have not been regulated in GR 5 of 2021. The presence of KBLIs that do not have a Ministry as their supervisor still requires agreement between Ministries/Institutions. The absence of Ministries/Institutions that serve as supervisors causes delays for Business Actors in starting their investment activities which can have a negative impact on Indonesia's efforts to achieve a nice rank for Ease of Doing Business. Meanwhile, BKPM provides a solution that is not a concrete step through the issuance of an unsupported KBLI determination for Business Actors who apply for one of the 353 unsupported KBLI.